Structure and Electrical Properties of the Thin Gold Leaves Fabricated by Vietnam Traditional Laminating Technology - Thuan, Nguyen Khac; Nhat, Hoang Nam (Communications in Physics, 2014)
The structure and electrical properties of the thin gold leaves fabricated by Vietnam traditional laminating technology are introduced. The gold leaves are usually created with the average size of 3x3cm, and 200nm thickness, they can easily be broken when handling carelessly. By the measurements of X-ray Diffraction (XRD), and Electron Scanning Microscopy (SEM), the structure and surface morphology were investigated. We have also measured the absorption spectra and determined the resistivity of the samples and found that the gold films possessed the Ca impurities stuck on the surface of the leaves. The conductivity of the films is relatively higher and the absorption maximum is red-shifted in comparison with that of the bulk.